2021
DOI: 10.1109/tcsvt.2020.3046881
|View full text |Cite
|
Sign up to set email alerts
|

Quality-Driven Variable Frame-Rate for Green Video Coding in Broadcast Applications

Abstract: The Digital Video Broadcasting (DVB) has proposed to introduce the Ultra-High Definition services in three phases: UHD-1 phase 1, UHD-1 phase 2 and UHD-2. The UHD-1 phase 2 specification includes several new features such as High Dynamic Range (HDR) and High Frame-Rate (HFR). It has been shown in several studies that HFR (+100 fps) enhances the perceptual quality and that this quality enhancement is contentdependent. On the other hand, HFR brings several challenges to the transmission chain including codec com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Furthermore, considering the frame rate, it is well known that lower frame rates lead to a reduced power consumption on versatile devices [12,16], but the amount of savings was not assessed. In [17], it was shown that depending on the video content, optimal frame rate estimates can be obtained to optimize the rate-distortion performance, however, the impact on the energy consumption was not discussed.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, considering the frame rate, it is well known that lower frame rates lead to a reduced power consumption on versatile devices [12,16], but the amount of savings was not assessed. In [17], it was shown that depending on the video content, optimal frame rate estimates can be obtained to optimize the rate-distortion performance, however, the impact on the energy consumption was not discussed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Frame rate reduction is mostly performed by frame averaging [17]. The reason is that using frame averaging, a capturing process is simulated where the shutter angle is maximized.…”
Section: Literature Reviewmentioning
confidence: 99%